Flat-topped emission centred at 1 250 nm from quantum dot superluminescent diodes - D. Childs; K.M. Groom; S.K. Ray; H.Y. Liu; M. Hopkinson; R.A. Hogg (South African Journal of Science, 2010)
We present a method for tailoring a broadband and flat-topped emission spectrum in quantum dot superluminescent diodes based upon modification of the dots-in-compositionally-modulated-well (DCMWELL) technique. We demonstrate flat-topped emission with 95 nm full width at half maximum (FWHM), centred at 1 250 nm, and with output power in excess of 8 mW.